EU enlargement, migration and labour market institutions - Per Lundborg (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2006)
This paper discusses free immigration to regulated labour markets (as in Europe) and to unregulated labour markets (as in the US), and explores the implications for migration flows of collective agreements, employment protection laws, product market regulations etc. It is argued that the European type of labour market institutions prevent wage dumping and restrict major immigration flows to periods of business peaks in the immigration country. Based on the empirical evidence on the differences in institutions, it is argued for instance that the UK and Ireland are likely to be exposed to larger wage effects than for instance Germany and Austria. Labour market institutions are likely to grow more similar across countries and stricter as a consequence of free mobility.
Keywords: 330; EU-Erweiterung; internationale Wanderung; Einwanderung - Auswirkungen; Arbeitsmigration; Arbeitsmarktentwicklung; institutionelle Faktoren; Regulierung; Tarifvertrag; Lohnpolitik; Gütermarkt; Wettbewerb; Arbeitsmarkt; Kündigungsschutz; Kündigungsrecht; Arbeitsrecht; europäische Integration; Konvergenz; Konjunkturaufschwung; Konjunkturabhängigkeit; Europäische Union